The identity of Phlomoides pararotata (Lamiaceae, Lamioideae) - Zhao, Yue; Chen, Ya-Ping; Liu, De-Tuan; Turdimatovich, Turginov Orzimat; Liang, Cun-Zhu; Xiang, Chun-Lei (Phytotaxa, 2021)
This paper presents a re-evaluation of the taxonomic identity of Phlomoides pararotata. Based on a comparative study of morphology and type material as well as field investigations, P. pararotata is synonymized with P. burmanica. Leaf features as well as bract morphology of this species are described.